PENGGUNAAN KALIMAT PERINTAH MEIREI DALAM DORAMA GREAT TEACHER ONIZUKA (SUATU KAJIAN SOSIOLINGUISTIK - Muhammad Wahyu Dirgantara; Nana Rahayu; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research discussed about the imperative sentence meirei in Geat Teacher Onizuka drama by Toru Fujisawa in 2010 years. The aim of this research is to know the kinds of imperative sentence meirei in Great Teacher Onizuka drama and using in Japanese people that finds in drama. The object of this research is the imperative sentence meirei in Great Teacher Onizuka drama. This research is a qualitative research which used descriptive method. The result of this research indicate there are six kinds of imperative sentence in this drama based of meirei no hyougen theory which are using imperative verb e, ro, shiro/koi, added nasai in verb and auxiliary, pattern o kudasai, add koto/youni after verb and adverb, descriptive sentence that to be imperative sentence by self te, imperative expression directly that impressed be explicit pattern te kudasai, te kure, and o negaimasu. Then, there are many user people’s group and relationship between user imperative sentence meirei is: intimate degree relationship, age, social relationship, status relationship, gender, in-group and out-group, situation.Keyword: Imperative sentence, meirei, drama, Great Teacher Onizuka, Sociolinguistics